PENTINGNYA PEMBENTUKAN KARAKTER PADA ANAK USIA DASAR - fatkhu rizqi; Lu’luil Maknun (FASHLUNA, 2021)
Character education, it is really needed not only at school but also at home, in a social environment. this is absolutely necessary for the life of this nation. Character education is a necessity in facing the challenges of globalization at this time. Character education has a high meaning from moral education because it does not just teach what is right and what is wrong, but helps children feel good values, are willing and able to do so. The formation of a child's personal character begins in the family. The family plays a very big role in character education because when the child is at home. Character education for students is considered very important to be implemented immediately in the education unit. The implementation will be more effective if the teacher places himself as an example for his students. This study uses a qualitative method by taking data from various sources and presenting the results of the analysis descriptively. Therefore this character education research is to develop students' abilities to make good, bad decisions, maintain, realize, and spread goals for everyday life with all their heart. The formation of the character of elementary school children can be done by instilling character values ​​consistently both when the child is in the family environment, school environment, and community environment. With this consistency, the expected character can be planted well so that a good character is formed. Character education is a deliberate effort to help optimally develop character.